A thermoelectric generator for scavenging gas-heat: From module optimization to prototype test. (15th February 2017) - Cheng, Fuqiang; Hong, Yanji; Li, Weiping; Guo, Xiaohong; Zhang, Hailong; Fu, Feng; Feng, Bingqing; Wang, Gang; Wang, Chao; Qin, Haibing
Abstract: Scramjets of hypersonic vehicles feature huge heat flux inside which can be harvested by thermoelectric devices as auxiliary power source. As a preliminary study to support scramjet-based thermoelectric generation, some work focusing on enhancing output power of thermoelectric generators (TEGs) was undertaken. Firstly, brief rules to increase TEG output power were summarized by analyzing a one-dimensional physical model. And thermoelectric modules adopting polycrystalline Bi2 Te3 -based materials prepared by mechanical alloy method with spark plasma sintering were fabricated with the figure-of-merits up to 1.13 (p-type) and 1.02 (n-type). Then a measuring system was built to test output performance of the modules and mounting pressure for the modules was optimized. Based on the system, influences of structure parameters of the modules including thermoelement thickness and cross-area on the output power were tested and analyzed experimentally. Using hot flowing air with temperature up to nearly 740 K as the gaseous energy source, a gas-heat scavenging TEG prototype was assembled and cyclically tested. Output power of 72.6 W was achieved for the TEG prototype and the corresponding area-specific power was 0.378 W·cm −2 for the thermoelectric pile consisting of six pairs of the Bi2 Te3 -based modules. At last, net output power considering power consumption of the coolant pump of the TEG prototype was analyzed. Highlights: Basic factors to enhance output power of TEGs are extracted. Geometries of thermoelectric modules are optimized experimentally. Area-specific power of a gas-heat scavenging TEG prototype is up to 0.378 W·cm −2 . Maximum net output power of the TEG prototype is optimized.